Desain Kompor Mobile Briket Batubara dan Biomassa Pada Daerah Bencana - Widodo sri; Meinarni Thamrin; Sufriadin -; Irzal Nur; Asran Ilyas; Monika Sroyer (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
Big flood disaster in South Sulawesi Province has occurred on January 22 and 23 2019. This event is one of the disasters that is quite severe for the City of Makassar and its surroundings. This incident encouraged the community service team to serve the community. Community service program UNHAS-Community Partnership Program (PPMU-PK-M) has partnered with one of the business units (UD Prima Teknik) which is engaged in fence welding and building maintenance needs. UD Prima Teknik is located in Antang Village, Manggala District, Makassar City. UD Prima Teknik is a partner who has helped the community service team in designing mobile stoves fueled with coal and biomass briquettes. The stove that has been designed has been socialized and used for cooking needs in meeting food needs in disasters areas. This stove is designed from iron, strong, resilient, and easy to carry anywhere (especially to disasters areas). The fuel used on the stove is coal, wood or wood charcoal (biomass) briquettes. The choice of fuel, besides being easy to carry on a trip, is also a very low risk of danger compared to gas stoves that are mostly used by the community at this time. If in conditions of limited fuel briquettes and wood charcoal, then this stove can also use wood fuel that is in the vicinity of the disaster area. In disaster conditions in an area, the difficulty that is often experienced by the community is the difficulty of the supply / assistance of ready-to-eat food because of limited kitchen facilities (tools for cooking).